An interaction model based on an interpretation of the first-quantized relativistic schrodinger equation - Khalid Md. Nor,; Ithnin Abdul Jalil,; Hassan Abu Kasim, (Universiti Kebangsaan Malaysia, 1996)
The relativistic Schrodinger equation is reinterpreted as describing a classical particle that mutually-interacts with other objects via electromagnetic-like gravity waves. The accompanying derivation equates the usual quantum mechanical energy and momentum operators to the effects of negative or attractive energy. Lorentz-like transformation equations are obtained that yield the uncertainty principle such that quantum uncertainty is ascribed to the disregard of a magnetic-like component of a gravity wave. Finally, quantum-level Maxwell-like equations that involve the above gravity waves are derived.